The solar cycle in the temperature of the tropical stratosphere - Ana G. Elias; Nieves Ortiz de Adler (Geofísica Internacional, 2004)
A search for a relationship between tropical stratosphere temperature anomalies at 10 hPa (~30 km), during 1964-1996 and the F10.7 cm solar flux has been carried out. The long-term trend and the Quasi-Biennial Oscillation influence over four seasonal and the annual temperature series were removed. The linear correlation coefficients, r, between temperature and F10.7 for the five series fall between 0.02 and 0.31, which suggests that the association between temperature and solar cycle is weak. However, when the data of each series are grouped according to solar cycle, temperature as a function of F10.7 shows a non-random behavior similar to a hysteresis loop. The sense of rotation, axis and area of a hysteresis loop are different for each solar cycle. The time shift between temperature and solar flux increases from cycle 20 to 22. The correlation between temperature and F10.7 becomes progressively lower from cycle 20 to 22. This suggests that the stratospheric temperature is determined not only by the solar flux, but also by parameters such as ozone and CO2, and feedback mechanisms between them.